Keterampilan Guru Dalam Bertanya Pada Pembelajaran Matematika - Nasution, Mariam (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2019)
In learning mathematics the questioning skills are very much needed in order to carry out the teaching and learning process in the classroom. Skills to ask, for a teacher is a very important skill to master. The skill of asking is an integral part in order to improve the quality of learning processes and outcomes, which is also part of the success in instructional management and classroom management. Through the skill of asking the teacher is able to detect obstacles in the process of thinking among students and can improve and improve the learning process among students. The questions that are conveyed must pay attention to the components, the skill component to ask. Therefore the questioning skills can be divided into two groups, namely basic questioning skills and advanced questioning skills. Basic questioning skills are: (1) Clear and concise, (2) Provision of references, (3) Concentration, (4) Transfer of turn, (5) Distribution, (6) Giving time to think (7) Giving guidance. Advanced questioning is: (1) Changing cognitive level guidance (2) Setting the order of questions, (3). Tracking questions, and (4) Encouraging interaction.